n = 0 ∑ ∞ 2 0 1 5 2 n − 2 0 1 5 − ( 2 n ) 1
If the closed form of the series above is in the form b a , where a and b are positive coprime integers, then find b − a .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
nice problem!
I did it using geometric series that turned it to a telescoping series.
Log in to reply
please tell how
Please relpy, how u did it
Log in to reply
I set it at level 4, but it has moved up to level 5 because the solve rate is only 8%.
Log in to reply
Hmm. Yeah, BTW, what's the actual trend of increment of the rating based on the solve rate? Any guess?
Log in to reply
@Kartik Sharma – I've never noticed a definite pattern, although I've occasionally noticed ratings change somewhat dramatically at the 10% solve rate. The algorithm that is used to determine ratings must be quite complicated, so while I'm still curious about how it works, I don't try that hard to figure it out. :)
I know it's a little bit overkill but I didn't see the telescoping initially so I did it in a more involved way:
X 1 − X − 1 1 + X 2 − X − 2 1 + X 4 − X − 4 1 + X 8 − X − 8 1 + ⋯
= X 2 − 1 X + X 4 − 1 X 2 + X 8 − 1 X 4 + X 1 6 − 1 X 8 + ⋯
= 2 1 ( X 1 + 1 1 + X 1 − 1 1 + X 2 + 1 1 + X 2 − 1 1 + X 4 + 1 1 + X 4 − 1 1 + X 8 + 1 1 + X 8 − 1 1 + ⋯ )
Now let A = X 1 + 1 1 + X 2 + 1 1 + X 4 + 1 1 + X 8 + 1 1 + ⋯ and B = X 1 − 1 1 + X 2 − 1 1 + X 4 − 1 1 + X 8 − 1 1 + ⋯
Then the answer to the original problem is thus 2 A + B
We observe that B = X − 1 1 + 2 1 ( − X 1 + 1 1 + X 1 − 1 1 − X 2 + 1 1 + X 2 − 1 1 − X 4 + 1 1 + X 4 − 1 1 − ⋯ )
B = X − 1 1 + 2 B − A
A + B = X − 1 1 + 2 B + A
2 B + A = X − 1 1
plug in X = 2 0 1 5 , 2 B + A = 2 0 1 4 1
Problem Loading...
Note Loading...
Set Loading...
The series can be written as
n = 0 ∑ ∞ 1 − x 2 n + 1 x 2 n = n = 0 ∑ ∞ ( 1 − x 2 n 1 − 1 − x 2 n + 1 1 ) ,
with x = 2 0 1 5 1 . This is now a telescoping series with sum
1 − x 1 − n → ∞ lim ( 1 − x 2 n + 1 1 ) = 1 − x 1 − 1 = 1 − x x .
Plugging in our value for x gives us the sum 1 − 2 0 1 5 1 2 0 1 5 1 = 2 0 1 4 1 .
Thus b − a = 2 0 1 4 − 1 = 2 0 1 3 .